Evaluasi Potensi Parasitoid Penggerek Pucuk Tebu, di Kabupaten Bantul - Eddy Mahrub; Sri Ambarwati Amini; Nugrahaning Rahayu (Jurnal Perlindungan Tanaman Indonesia, 2000)
The objective of the research is to evaluate the potency of sugar cane top borer parasitoids whether the parasitoids are available from the released individuals produced previously in the laboratory or other species naturally exist in the field. The result showed that Trichogramma sp. which have been released did not attack sugar cane top borer eggs. Tetrastichus schoenobii and Telenomus rowani observed in the field were seemingly replacing the role of Trichogramma sp. parasitoid previously released in the area. Both the T. schoenobii and T. rowani attacked the sugar cane top borer eggs with parasitism of 34.59% and 24.07% respectively. Larval parasitoids were Elasmus zehntneri, Rhaconotus scirpophagae, Stenobracon nicevillei and Allorhogas sp. while pupal parasitoid was Isotima javensis. Larval parasitism was 0-41.00% averagely. The most dominant parasitoid was R. scirpophagae with parasitism of 18.75% followed by E. zehntneri with parasitism of 17.25% respectively. Total parasitism by all species were 37.59% in young plant and 23.90% in old plant respectively. Pupal parasitism on young and old plants were 13.66% and 8.26% respectively. Those parasitoids were available in the field naturally and performed important potentiality in the natural control of sugar cane top borer. Those above mentioned parasitoids need to be conserved by preventing the ecosystem suffering from any hazardous changes, which may afflict negative effects to the natural enemies.